Effect of indole-3-carbinol on transcriptional profiling of wound-healing genes in macrophages of systemic lupus erythematosus patients: an RNA sequencing assay. (July 2020) - Eghbalpour, Farnaz; Aghaei, Mehrdad; Ebrahimi, Mansour; Tahsili, Mohammad Reza; Golalipour, Masoud; Mohammadi, Saeed; Yazdani, Yaghoub
Background: Relapses and flares with delayed wound healing are among the main symptoms of systemic lupus erythematosus (SLE), a rheumatic autoimmune disease. The orientation of immune responses in SLE disease depends on the function of the population of macrophages. This study investigated the effect of indole-3-carbinol (I3C) on transcriptional profiling of macrophage-derived monocytes (MDMs) in four stages of the wound-healing process. Methods: In the first phase of study, MDMs were generated from peripheral blood mononuclear cells of three new SLE cases (unmedicated) and two healthy controls. The cases and controls were then divided into I3C treated and untreated groups after 24 hours of exposure to I3C. Single-end RNA sequencing was performed using an Illumina NextSeq 500 platform. After comprehensive analysis among differentially expressed genes, CDKN1A, FN1 and MMP15 were validated by quantitative real-time polymerase chain reaction as upregulated ranked genes involved in wound-healing stages. Results: The RNA sequencing analysis of treated cases and treated controls versus untreated cases and untreated controls (group 3 vs. group 4) revealed upregulation of various genes, for example: C1S, C1R, IGKV1-5, IGKV4-1, SERPING1, IGLC1 and IGLC2 in coagulation; ADAM19, CEACAM1 and CEACAM8 in M2 reprogramming; IRS1, FN1, THBS1 and LIMS2 in extracellular matrix organization; and STAT1, THBS1 and ATP2A3 in the proliferation stage of wound healing. Conclusions: The results showed that treatment with I3C could modulate the gene expression involved in wound healing in SLE cases and healthy controls.